Social justice in employment and remuneration of workers in Cameroon in the light of the parable of the Workers in the Vineyard (Mt 20:1-15) : An African Biblical Interpretation - Van Eck, Ernest (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2020.